Carsick : John Waters hitchhikes across America - Waters, John, 1946- (Farrar, Straus and Giroux, 2014)
"John Waters is putting his life on the line. Armed with wit, a pencil-thin mustache, and a cardboard sign that reads 'I'm not psycho,' he hitchhikes across America from Baltimore to San Francisco, braving lonely roads and treacherous drivers. But who should we be more worried about: the delicate film director with genteel manners or the unsuspecting travelers transporting the Pope of Trash?"--Dust jacket flap.